Farmaci antipertensivi a confronto: costi e benefici per il paziente e la collettività - Costa, Francesco Vittorio (Farmeconomia. Health Economics and Therapeutic Pathways, 2003)
Pharmacoeconomic analysis of antihypertensive treatment should be performed following a correct methodological evaluation and considering with accuracy both costs and benefits of different therapeutic options. Costs evaluation is frequently performed simply examining the retail price of drugs which represents only a part (usually no more than 50%) of cumulative costs of therapy. Controlled clinical trials are the main source of information about benefits of therapy, but probably, in many cases, they underestimate the benefits of treatment and are unable to differentiate the effects of different drugs because of a too short follow-up. Benefits should be calculated not only in terms of saved lives or prevented events, but also in terms of prevention-regression of target organ damage and of quality of life of patients. If analysis are performed correctly, more recent drugs, like ATII antagonists, even if they have a higher retail price, become highly costeffective thanks to their protective activity against events, and to unbeatable levels of compliance and persistence which are associated with treatment with these drugs. Comparison between old (cheaper) and newer (more expensive) drugs, and recommendations to start therapy with the cheaper drugs, are a nonsense since to achieve goal blood pressure combinations of more drugs are always necessary. Treatment of hypertension, if extended to all patients and performed aggressively, must be considered not only a life-saving, but also a money-saving tool.